Hormone Replacement Therapy And Breast Cancer- A Case Control Study (Bangladesh Medical Journal, 2012)
The present study was undertaken to asses any association between hormone replacement therapy (HRT) and breast cancer. This hospital based case -control study was conducted among sixty cases of diagnosed female breast cancer patients and age matched seventy controls of women without breast cancer and any breast complaints (pain or lump in the breast, any discharge through the nipple) during the period of January to June 2009. Data was collected at National Institute of Cancer Research, Hospital (NICRH), Mohakhali, Dhaka, Ahsania Mission Cancer Hospital, Mirpur, Dhaka, and Delta Medical college Hospital Mirpur Dhaka. Controls were selected from the women who attended those hospitals for other treatment and relatives of the breast cancer patients. The findings revealed cases (30%) took hormone therapy in comparison to the controls (7.1%) and this difference was statistically significant ( 2test, p